Online journalism from the periphery : interloper media and the journalistic field - Eldridge, Scott A. (Routledge, 2018)
Online Journalism from the Periphery looks at how a range of new media actors, communicating online, have challenged us to think differently about the journalistic field. Emerging from the disruption of digital technology, these new actors have been met with resistance by an existing core of journalism, who perceive them as part of a ‘digital threat’ and dismiss their claims of journalistic belonging. As a result, cracks are appearing in the conceptual foundations of what journalism is and should be.